2021
DOI: 10.1121/10.0006209
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of the earplug contribution to the low-frequency objective occlusion effect induced by bone-conducted stimulation

Abstract: The use of earplugs is commonly associated with an increased perception of the bone-conducted part of one's own physiological noise. This phenomenon is referred to as occlusion effect and is most prominent at low frequencies. Several factors influence the occlusion effect, such as the ear anatomy; the bone-conducted stimulation; and the type of occlusion device and its fit, insertion depth, and material properties. The latter factor is of great interest to potentially reduce the occlusion effect of passive ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…For this purpose, the artificial ear includes skin, cartilaginous and bony parts surrounding a cylindrical earcanal of length 29 mm and radius 3.75 mm. Note that the treatment of the earcanal as a cylinder with constant radius does not change the basics of bone-conducted acoustic wave propagation 5 7 , at least at low frequencies, compared to a realistic 3D shaped earcanal but greatly simplifies the experimental setup. For further details about the artificial ear used in this work and the associated experimental setup, the reader is referred to “ Sample manufacturing and experiments ” section.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For this purpose, the artificial ear includes skin, cartilaginous and bony parts surrounding a cylindrical earcanal of length 29 mm and radius 3.75 mm. Note that the treatment of the earcanal as a cylinder with constant radius does not change the basics of bone-conducted acoustic wave propagation 5 7 , at least at low frequencies, compared to a realistic 3D shaped earcanal but greatly simplifies the experimental setup. For further details about the artificial ear used in this work and the associated experimental setup, the reader is referred to “ Sample manufacturing and experiments ” section.…”
Section: Resultsmentioning
confidence: 99%
“…Above this frequency, the occlusion effect induced by the meta-earplug remains lower than 5 dB. Regarding the silicone and the foam earplugs, their difference in occlusion effect is deemed to come from their difference in Poisson’s ratio 7 , which influences the vibro-acoustic contribution of their medial surface to the sound pressure level generated in the occluded earcanal. For the meta-earplug, the occlusion effect reduction rather comes from the acoustic properties of its medial surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The earplugs used in this study were made of silicone, and filling the ear canal with silicone earplugs might have changed the shape of the peripheral transmission medium, resulting in a change in the propagating component, which might have changed the osseotympanic component and generated a difference in ECSP. Carillo et al (2021) showed that silicone earplugs impose a higher volume velocity than urethane foam earplugs, the difference in ECSP is larger for silicone earplugs, and the spatial distribution of ear canal wall vibration is affected by changes in the shape of the surrounding tissue, which affects OE. 33) The difference between the OE and the difference in the ECSP is due to the resonance of the cavities and bones, as mentioned earlier.…”
Section: Comparison Among the Oe Difference In The Ecsp And Osseotymp...mentioning
confidence: 99%
“…Carillo et al (2021) showed that silicone earplugs impose a higher volume velocity than urethane foam earplugs, the difference in ECSP is larger for silicone earplugs, and the spatial distribution of ear canal wall vibration is affected by changes in the shape of the surrounding tissue, which affects OE. 33) The difference between the OE and the difference in the ECSP is due to the resonance of the cavities and bones, as mentioned earlier. Although bone and cavity resonances have been mentioned, they were not measured directly in this study.…”
Section: Comparison Among the Oe Difference In The Ecsp And Osseotymp...mentioning
confidence: 99%